ANALYSIS OF THE IMPLEMENTATION of COORDINATION in the EXECUTION of PLENARY MEETINGS of MEMBERS of the REGIONAL PEOPLE’S REPRESENTATIVE COUNCIL (DPRD) of LAMPUNG PROVINCE - Regina Alifia Pratana; Malik (International Journal of Multidisciplinary Reseach, 2026)
The research method used is descriptive qualitative research. This method is used to describe the implementation of coordination in the Plenary Meeting of Members of the Lampung Provincial People's Representative Council (DPRD). All data were obtained directly from informants in the field using interviews and document studies. The results of the study indicate that, in the dimensions of (a) Inter-Institutional Synchronization, synchronization between institutions still faces serious challenges, particularly related to the lack of agenda integration between the DPRD and the executive branch. (b) Information Management, information management has not been optimally coordinated. (c) Collaboration between Implementers: A collaborative work culture has not yet been established. Inhibiting aspects include: (a) Synchronization between Institutions: Differences in political and institutional interests between the Regional People's Representative Council and its executive counterparts. (b) Information Management: Information delivered late or in a partial manner, leaving DPRD members unprepared for meetings. (c) Collaboration between Implementers: A sectoral work culture, where each work unit (commission, faction, secretariat) focuses more on its individual tasks than on shared goals.